The Teaching Materials of Youth Novels Loaded with Moral Values for High School - Evi Supriatin; Rizal Ibrahim Aji; Suherli Kusmana (Widyantara, 2023)
This study aims to address the problem of the quality of Indonesian language learning. The problem in question is the availability of novel text teaching materials in both printed and online Indonesian language textbooks. Digital teaching materials can streamline learning and students are not mistaken in interpreting the moral values ​​of a novel. This research uses research and development methods. Based on the study of novel text learning carried out, it is known that teachers need teaching materials that can overcome the teacher's difficulties in showing examples that are easily accessible to students. From the study of youth novels, the novel "Pesantren Impian, Rumah Tanpa Jendela, dan Cinta di Ujung Sajadah" has a moral message as life values ​​so that it can be used as examples of novel texts on digital teaching materials. Based on expert validation of the material or content components, presentation, language, and graphics in digital novel teaching materials, it is declared valid (84.89). The trial carried out in this study was a feasibility test by seven Class XII Indonesian teachers from various schools because students were learning from home as a government policy in overcoming the impact of the Covid-19 pandemic. From the feasibility test of using teaching materials, it is known that digital novel teaching materials are feasible to be used in learning, especially when using an online learning approach.